2022
DOI: 10.1038/s41533-022-00268-w
|View full text |Cite|
|
Sign up to set email alerts
|

The 1-minute sit-to-stand test to detect desaturation during 6-minute walk test in interstitial lung disease

Abstract: Although the 6 min walk test (6MWT) is well-established for assessing desaturation in patients with interstitial lung disease (ILD), it cannot be easily performed in primary healthcare settings. This retrospective observational study aimed to evaluate the usefulness of the 1 min sit-to-stand test (1STST) for assessing desaturation during 6MWT in ILD patients with normal resting blood oxygen levels. We included 116 patients, and the pulse oxygen saturation (SpO2) for both methods was analyzed. The SpO2 nadir du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
3
4
0
1
Order By: Relevance
“…This difference could be due to variations in the body stature as well as due to difference in the extent of ILD in the mentioned studies. On the other hand, number of repetitions in 1-STST was comparable to previous studies ( Oishi et al, 2022 ; Briand et al, 2018 ; Tremblay Labrecque et al, 2020 ). On comparing, a moderate degree of correlation ( r =0.48, P <0.001) was seen between 6MWD and number of 1-STST repetitions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This difference could be due to variations in the body stature as well as due to difference in the extent of ILD in the mentioned studies. On the other hand, number of repetitions in 1-STST was comparable to previous studies ( Oishi et al, 2022 ; Briand et al, 2018 ; Tremblay Labrecque et al, 2020 ). On comparing, a moderate degree of correlation ( r =0.48, P <0.001) was seen between 6MWD and number of 1-STST repetitions.…”
Section: Discussionsupporting
confidence: 89%
“…Fifty-six subjects (93.3%) were consistently grouped by both 6MWT and 1-STST based on oxygen desaturation of ≥4% or less, (κ=0.56; 95% CI, 0.30-0.82). Previous studies also showed a similar trend but with a higher degree of agreement (0.68-0.82) (Briand et al, 2018;Oishi et al, 2022;Tremblay Labrecque et al, 2020). The above results strongly suggest that both 6MWT and 1-STST are equally reliable in detecting changes in SpO2 in ILD patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Of late, the 1-min sit-to-stand test (1STS) has gained popularity. Significant correlations were seen between distance walked during 6MWT and number of repetitions on 1STS, as well similarities in maximal oxygen uptake, nadir S pO 2 and frequency of desaturation [38][39][40], suggesting that the 1STS may offer a simpler alternative to the 6MWT, with potential for primary care use. However, responsiveness to acute oxygen administration has not been demonstrated.…”
Section: Introductionmentioning
confidence: 87%
“…Details of the COVID-19 restrictions throughout the study period are summarised in the e-supplement. Including the 6 min walk test (6MWT) [ 21 ] which was conducted in person or the 1-minute sit-to-stand (STS) conducted remotely [ 22 , 23 ]. For the one-minute STS participants were instructed to use a stable kitchen or dining room chair.…”
Section: Intervention - Pulmonary Rehabilitationmentioning
confidence: 99%